PAJAK PENGHASILAN ATAS DIVIDEN DALAM UNDANG-UNDANG CIPTA KERJA - ,; , (Bilancia : Jurnal Ilmiah Akuntansi, 2021)
ABSTRACT The Job Creation Law contains changes to laws of various scopes. One of the amended provisions is the tax exemption on dividends. The purpose of this research  was to determine the background of changes in provisions on dividend tax, changes in dividend taxation mechanism, and requirements for exemption of dividends from tax objects. The method used in this research is qualitative. Based on the results of the research, the tax exemption on dividends is an effort by the government to encourage domestic investment caused by the bad impact of the Covid-19 pandemic and the slowdown in the world economy. Before the issuance of the Job Creation Act, dividends were an object of income tax which were subject to final rates for individual taxpayers and non-final for corporate taxpayers. To exempt dividends from being taxed, the dividends must be invested in Indonesia. Dividends can be invested in the financial sector as well as the non-financial sector.   ABSTRAK Undang-undang Cipta Kerja berisi perubahan undang-undang dari berbagai ruang lingkup. Salah satu ketentuan yang diubah adalah pengecualian pajak atas dividen. Tujuan dari penelitian ini adalah untuk mengetahui latar belakang perubahan ketentuan atas pajak dividen, perubahan mekanisme pemajakan dividen , dan persyaratan pengecualian dividen dari objek pajak. Metode yang digunakan pada penelitian ini adalah kualitatif. Berdasarkan hasil penelitian, pengecualian pajak atas dividen merupakan upaya pemerintah untuk  mendorong investasi di dalam negeri yang disebabkan oleh dampak buruk pandemi Covid-19 dan perlambatan ekonomi dunia. Sebelum diterbitkannya Undang-Undang Cipta Kerja, dividen merupakan objek pajak penghasilan yang dikenakan tarif final untuk wajib pajak orang pribadi dan nonfinal untuk wajib pajak badan. Untuk membebaskan dividen dari pengenaan pajak, dividen tersebut harus diinvestasikan di Indonesia. Dividen dapat diinvestasikan ke dalam sektor keuangan maupun sektor nonkeuangan.